2013
DOI: 10.3109/08916934.2013.834495
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic control of the epigenome in systemic Lupus erythematosus

Abstract: Epigenetic mechanisms are proposed to underlie aberrant gene expression in systemic lupus erythematosus (SLE) that results in dysregulation of the immune system and loss of tolerance. Modifications of DNA and histones require substrates derived from diet and intermediary metabolism. DNA and histone methyltransferases depend on S-adenosylmethionine (SAM) as a methyl donor. SAM is generated from adenosine triphosphate (ATP) and methionine by methionine adenosyltransferase (MAT), a redox-sensitive enzyme in the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 115 publications
2
35
0
Order By: Relevance
“…Studies in syngeneic mice have shown that injecting demethylated DNA into CD4+ T cells with can precipitate a lupus-like syndrome(39, 40). The role of underlying metabolic mechanisms in modifying gene expression in SLE is also proposed (41). Oxidative stress likely also contributes to SLE pathogenesis, and has been shown to inhibit ERK pathway signaling in T cells leading to DNA demethylation, upregulation of immune genes and autoreactivity (42*).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in syngeneic mice have shown that injecting demethylated DNA into CD4+ T cells with can precipitate a lupus-like syndrome(39, 40). The role of underlying metabolic mechanisms in modifying gene expression in SLE is also proposed (41). Oxidative stress likely also contributes to SLE pathogenesis, and has been shown to inhibit ERK pathway signaling in T cells leading to DNA demethylation, upregulation of immune genes and autoreactivity (42*).…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria are the dominant source of ATP. Mitochondrial dysfunction and ATP depletion have been reported in lupus CD4 + T cells, which inhibits the mTOR pathway and modifies epigenetic pathways, including methylation, demethylation, and histone phosphorylation, and mediates enhanced T cell activation in SLE (Oaks and Perl, 2014). Therefore, metabolic control of epigenetic dynamics may play a leading role in the pathogenesis of SLE.…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%
“…1 SLE patients have elevated concentrations of pro-inflammatory cytokines such as IL-6, TNF-a and IL-1 which contribute to the inflammatoryprocess. 2 Cardiovascular disease (CVD) risk is at least doubled among SLE patients compared with the general population.…”
Section: Introductionmentioning
confidence: 99%